2020
DOI: 10.21203/rs.3.rs-30701/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic Immune-Inflammatory Index predicts prognosis of patients with COVID-19: a retrospective study

Abstract: Background Our study aimed to investigate the prognostic value of a novel inflammatory index, systemic immune-inflammation index (SII), with the clinical outcomes of patients infected with coronavirus disease 2019 (COVID-19).Methods We evaluated a cohort study of COVID-19 patients (18–95 years old) in Tongji Hospital of Huazhong University of Science and Technology from January 28th 2020 to February 29th 2020. The enrolled patients were divided into two groups (including low-SII group and high-SII group) accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…16,17 However, there are a few studies investigating the predictive role of SII in the prognosis of COVID-19. 20,33 In those studies, the SII levels were high in patients who died at the hospital and who developed ARDS. In our study, SII was significantly specificity for prediction of the disease severity in COVID-19.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…16,17 However, there are a few studies investigating the predictive role of SII in the prognosis of COVID-19. 20,33 In those studies, the SII levels were high in patients who died at the hospital and who developed ARDS. In our study, SII was significantly specificity for prediction of the disease severity in COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“… 16 , 17 , 18 , 19 However, there are only a very few studies investigating the role of SII in reflecting the inflammatory status and prediction of prognosis in COVID‐19 patients. 20 PNI and SII markers are helpful predictors for COVID‐19 patients.…”
Section: Introductionmentioning
confidence: 97%
“…SII, which depends on the number of lymphocytes, neutrophils, and platelets, is an indicator associated with inflammation and can reflect the immune and inflammatory state [12]. Some studies have identified a clear correlation between SII and prognosis in malignancy and inflammatory conditions [13,14]. However, there are limited data about the benefit of SII in assessing the prognosis in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we dichotomized the continuous variables above/below the median and summed for each patient the single variables in order to have a score that could assume values from 0 (low risk) to 10 (high risk) (CLINICAL). To this, we added as variable for multivariate analysis the Total affected lung V% (VOLUME) and Systemic Inflammatory response Index as a surrogate of all laboratory test included in the manuscript (calculated by: platelet counts × neutrophil counts/lymphocyte counts) (INFLA) as suggested by recent publications to be a remarkable prognostic indicator to assess the in-hospital mortality and the development of respiratory complications in patients with COVID-19 [ 11 , 12 ]. The performance of the predictive models, singles and composite (MODEL 1 including all clinical, laboratory and CT variables) were assessed using receiver operating characteristic analysis (ROC), and the area under the curve (AUC) values were compared using the DeLong test.…”
Section: Methodsmentioning
confidence: 99%